2023
DOI: 10.1177/10567879231169709
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Coping Mechanisms in Graduate Occupational Therapy Students During the COVID-19 Pandemic and Civil Unrest Period: A Descriptive Study

Abstract: Objective: The COVID-19 pandemic and the sociopolitical climate in the United States have imposed additional stress and anxiety for graduate students. We explored the stress level in graduate occupational therapy students, the role of exercise in reducing stress, and common coping mechanisms applied to manage academic and sociopolitical stress. Methods: A survey was created and distributed to graduate occupational therapy students in the U.S. Results: Most participants reported moderate to high levels of acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Most of the visible minority TCEs from all backgrounds affirmed meditation and exercise was important tactic that inhibited stressful thoughts associated with their employment and caregiving services. Equivalently, a descriptive study by Hamed et al [ 83 ] reported that physical exercise is a good coping mechanism that helps decrease stress, anger, and frustration. Although not exclusive to transnational care, research by Dyrbye et al [ 84 ], Singh and Afroz [ 85 ], and Jadhav [ 86 ] illustrates that exercise alleviates burnout and that individuals who stay physically active have low levels of depression, anxiety, and stress levels in comparison to those with sedentary lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the visible minority TCEs from all backgrounds affirmed meditation and exercise was important tactic that inhibited stressful thoughts associated with their employment and caregiving services. Equivalently, a descriptive study by Hamed et al [ 83 ] reported that physical exercise is a good coping mechanism that helps decrease stress, anger, and frustration. Although not exclusive to transnational care, research by Dyrbye et al [ 84 ], Singh and Afroz [ 85 ], and Jadhav [ 86 ] illustrates that exercise alleviates burnout and that individuals who stay physically active have low levels of depression, anxiety, and stress levels in comparison to those with sedentary lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…Graduate students are also six times more likely to be depressed than the general population [ 5 ]. Some studies have found an increase in emotional distress of college students in China, and India, and a decline in mental health in the UK before, and during the COVID-19 outbreak [ 6 8 ], and a North American study found that occupational therapy masters students reported some academic related stress, long hours of study, examinations, and long lectures [ 9 ]. Moreover, the level of academic pressure has increased even more after the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] As for coping with stress, some students choose to limit food intake, choose unhealthy eating, or overeating, 67.55% of the students believed that physical exercise could effectively relieve stress, especially the decompression effect of taekwondo. In addition, social participation or talking with family, and friends could also be considered as a coping behavior [ 9 ]. It has been suggested that depression in graduate students affects research motivation, concentration, memory, creativity, and participation in research [ 11 ], which are not addressed timely, and effectively, will affect their studies, and personal lives, leading to other extreme behavior [ 12 ].…”
Section: Introductionmentioning
confidence: 99%